A randomized controlled trial of meditation and health education on carotid intima-media thickness and major adverse cardiovascular events in Black men and women - Norris, Keith C.; Salerno, John; Bairey Merz, C. Noel; Kaushik, Vidya; Gelleta, Simon; Castillo, Amparo; Nidich, Sanford; Gaylord-King, Carolyn; Schneider, Robert H. (Frontiers in Medicine, 2025)
IntroductionBlack Americans suffer from disproportionately high rates of cardiovascular disease (CVD). Psychosocial stress contributes to this disparity. Previous studies reported that the Transcendental Meditation (TM) technique reduced CVD risk factors, surrogate endpoints, and clinical events in high-risk populations. However, no study has evaluated the effects of stress reduction with meditation on surrogate CVD markers such as carotid intima-media thickness (cIMT) along with CVD clinical events. Therefore, this randomized clinical trial evaluated the long-term effects of meditation and health education (HE) on cIMT and CVD events in high-risk Black adults.Materials and methodsParticipants were Black women and men with CVD or at high risk who were randomized to either TM or HE. The primary outcome was a change in cIMT measured using B-mode ultrasound at baseline and 12 months. The main secondary outcome was major adverse cardiovascular events (MACE) at 5 years (maximum) of follow-up. Other secondary outcomes were MACE at 1 and 10 years of follow-up, blood pressure, and serum lipids after 1 year. Exploratory variables were a comparison of cIMT changes to historical controls and MACE after 14 years.ResultsThere were 197 randomized participants, of whom 136 completed posttest for cIMT. After 1 year, the TM and HE groups showed average cIMT changes of −0.0004 and −0.0003 mm, respectively, with no significant difference between the groups. Additionally, there were no significant differences between the groups in lipid levels or BP. However, both TM and HE groups showed prevention of progression of cIMT compared to historical controls at 12 months. In the survival analysis of MACE, there was a 65% relative risk reduction in the TM group after 5 (maximum) years of follow-up (HR = 0.346; 95% CI = 0.134–0.893; p = 0.017). At 1 and 10 years of follow-up, there were significant risk reductions in the TM vs. HE group, which was not significant at 14 years (all yearly maximums).DiscussionBoth treatment groups demonstrated prevention of progression of cIMT over 12 months compared to historical controls. However, the TM group showed a relative risk reduction for MACE of 65% at 5 years. Therefore, as a lifestyle modification method, TM may be useful in the secondary prevention of CVD in this and possibly other high-risk groups.Clinical trial registrationClinicalTrials.gov, NCT05642936.